Assay Of Paracetamol Syrup In Different Storage Temperatures By High Performance Liquid Chromatography - Dian Maria Ulfa; Dodi Irawan (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
Paracetamol formulated in solution, can be hydrolyzed to p-aminophenol, then can be broken down again into quinone-imin. The decomposition rate of paracetamol increases when the temperature is raised and if it is exposed to light directly. The habit of people in storing drugs after the packaging is opened and will be used again raises concerns about the quality of the drugs contained in the drug. The purpose of this study was to determine the level of paracetamol stored at room temperature and chiller temperature using the High Performance Liquid Chromatography (HPLC) method. The study was conducted by testing the levels of paracetamol syrup on the first day and after being stored for three days. Samples were divided into two groups of storage temperatures, room temperature and chiller temperature. The HPLC system used is the L1 column, the mobile phase water-methanol P mixture (3: 1), the flow rate 1.5. The average paracetamol levels at day 1 storage at room temperature and chiller temperature were 104.61% and 102.38%. The average paracetamol levels at day 3 storage at room temperature and chiller temperature were 102, 44% and 98.81%. Storage of paracetamol syrup at the chiller temperature produces smaller levels than at room temperature. Storage for three days shows a significant decrease in levels both at room temperature or chiller temperature (pvalue <0.05).